Kentucky Barns : Agricultural Heritage of the Bluegrass - Peachee, Carol (Book collections on Project MUSE., 2019)
"From horses to tobacco to bourbon, the barn is at the heart of Kentucky's heritage and industry and is a staple of the Bluegrass landscape. In Kentucky Barns: Agricultural Heritage of the Bluegrass, Carol Peachee showcases the barns in exquisite high-dynamic-range photography. From elegant Thoroughbred farms to historical treasures like the 1803 stone barn of Runnymede Farm in Bourbon County, Peachee travels across the state to capture and preserve the diverse architecture, heritage, and design that make these structures special. A beautiful tribute to the legacy of the Bluegrass State, Kentucky Barns features nearly 400 full-color photos of both the interior and exterior of these beautiful and functional icons of American culture and industry"--